2022
DOI: 10.1002/1873-3468.14538
|View full text |Cite
|
Sign up to set email alerts
|

Longin domain GAP complexes in nutrient signalling, membrane traffic and neurodegeneration

Abstract: Small GTPases act as molecular switches and control numerous cellular processes by their binding and hydrolysis of guanosine triphosphate (GTP). The activity of small GTPases is coordinated by guanine nucleotide exchange factors (GEFs) and GTPase activating proteins (GAPs). Recent structural and functional studies have characterized a subset of GAPs whose catalytic units consist of longin domains. Longin domain containing GAPs regulate small GTPases that facilitate nutrient signalling, autophagy, vesicular tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 70 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…Assuming that Vps28-C interacts with ESCRT-II, these proteins could associate with ESCRT-II without the involvement of any core ESCRT-I subunits. The presence of longin suggests that these proteins can activate small GTPases, which regulate many cellular pathways related to nutrient signaling and vesicular trafficking ( 68 ). Additional domains found in these proteins include TPR repeats, IG-like domains, and HTH/PCI domains which can be involved in interactions with protein substrates for further trafficking ( 69 71 ).…”
Section: Resultsmentioning
confidence: 99%
“…Assuming that Vps28-C interacts with ESCRT-II, these proteins could associate with ESCRT-II without the involvement of any core ESCRT-I subunits. The presence of longin suggests that these proteins can activate small GTPases, which regulate many cellular pathways related to nutrient signaling and vesicular trafficking ( 68 ). Additional domains found in these proteins include TPR repeats, IG-like domains, and HTH/PCI domains which can be involved in interactions with protein substrates for further trafficking ( 69 71 ).…”
Section: Resultsmentioning
confidence: 99%
“…No interactions have been yet detected for C9orf72 with either FLCN and FNIP1-2, indicating that there is specificity for the formation of two distinct complexes within this subfamily of DENN domain proteins: the FLCN/FNIP1-2 complex and the C9orf72/SMCR8/WDR41 complex (Amick et al, 2016). The structural orientation of the C9orf72/SMCR8/WDR41 complex is also reminiscent of FLCN/FNIP1-2, which suggested it might possess GAP activity (Jansen and Hurley, 2023). Then, these two different protein ensembles act at lysosomes with functions that seem related but distinct and that have yet to be elucidated (Amick and Ferguson, 2017;Jansen and Hurley, 2023; Figure 1C).…”
Section: Discussionmentioning
confidence: 99%
“…An exception to this rule are GAPs that contain longin/roadblock domains, which inactivate different GTPases: GTPase‐activating protein activity toward Rags (GATOR)1 and folliculin (FLCN)/FNIP in mechanismic target of rapamycin (mTOR)C‐controlled nutrient signaling, which inactivate the atypical RagA and RagC GTPases, respectively, the C9orf72:SMCR8 complex, a newly discovered GAP for trafficking Arf GTPases involved in amyotrophic lateral sclerosis, and mutual gliding‐motility protein B [MglB], which inactivates the bacterial small GTPase MglA to control bacterial motility. Jansen and Hurley discuss how cryo‐EM revealed that both GATOR1 and FLCN/FNIP, though binding to their cognate Rag GTPases in distinct manners, have both an inhibitory and a productive binding mode, predicted to respond to an increase or decrease in nutrients [7]. By contrast, the orientation of the longin domain of C9orf72 with respect to Arf is reminiscent of FLCN/folliculin‐interacting protein, which led to the hypothesis, then the confirmation using purified proteins, that it is an ArfGAP [7].…”
mentioning
confidence: 99%
“…Jansen and Hurley discuss how cryo-EM revealed that both GATOR1 and FLCN/FNIP, though binding to their cognate Rag GTPases in distinct manners, have both an inhibitory and a productive binding mode, predicted to respond to an increase or decrease in nutrients [7]. By contrast, the orientation of the longin domain of C9orf72 with respect to Arf is reminiscent of FLCN/ folliculin-interacting protein, which led to the hypothesis, then the confirmation using purified proteins, that it is an ArfGAP [7]. As discussed by Dinet and Mignot, bacterial MglB is also an atypical GAP that can bind to MglA in both an inhibitory and a productive manner, with the remarkable property that it is upregulated by MglA-GDP [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation